Meta-analysis of the effect of rituximab in the treatment of primary central nervous system lymphoma - Yavuz, S.; Yildirim, M.; Yazici, G.; Kaya, V.; Paydas, S. (OXFORD UNIV PRESS, 2017)
42nd European-Society-for-Medical-Oncology Congress (ESMO), Madrid, SPAIN, SEP 08-12, 2017